Comparison of the production behavior of regret-averse and purely risk-averse firms - Guo, Xu; Wong, Wing-Keung (Estudios de Economía, 2019)
Previous studies focused on the comparison of the optimal output levels of regret- averse firms under uncertainty and firms under certainty. This paper extends the theory by further investigating the effects of regret-aversion on production. We compare the optimal output levels of regret-averse firms with purely risk- averse firms under uncertainty and firms under certainty. We first show that the linear-regret firms will surely produce more than their purely risk-averse counterparts and surely produce less than firms under certainty. Thereafter, we give sufficient conditions to ensure the regret-averse firms to produce more than the purely risk-averse counterparts and study the comparative statics of the optimal production. We also develop properties of regret-aversion on production.